Reforming the global financial architecture - Ahluwalia, Montek S. (Commonwealth Secretariat LondonGB, 2000)
Identifies the key issues in reforming the international financial system and the extent of consensus in each area, and provides an assessment of the extent to which the initiatives being considered will help make the system less vulnerable to crises.